Human Resource Scorecard for Measuring Hospital Human Resource Performance: An Instrument Study at RSUP dr Ben Mboi Kupang - I Komang B R Desmon Logo; Qurratul Aini (PT Keberlanjutan Strategis Indonesia, 2026)
Strategic measurement of hospital human resources is needed because administrative indicators alone cannot explain the contribution of workforce management to service quality and operational performance. This study aims to develop and initially evaluate a Human Resource Scorecard instrument to measure human resource performance at Dr. Ben Mboi General Hospital, Kupang. Methods: This study reports the quantitative instrument assessment phase of a broader exploratory sequential mixed methods study. Quantitative data were collected using purposive sampling from 200 respondents consisting of healthcare workers, administrative staff, and managerial personnel. The study employed confirmatory factor analysis or structural equation modeling. The results indicate that the Human Resource Scorecard Instrument for Dr. Ben Mboi General Hospital, Kupang, demonstrated acceptable initial item validity and strong internal consistency reliability. The overall Human Resource Scorecard level was moderate, indicating that human resource management practices have been implemented but still require targeted improvement. Performance and productivity were the strongest dimensions, while compensation and rewards were the weakest. Occupational safety and well-being also require managerial attention, particularly through working hours, workload, number of patients per shift, staffing adequacy, and prevention of workplace violence. These findings suggest that hospital human resource performance measurement should include strategic dimensions related to workforce capability, engagement, leadership, reward fairness, safety, well-being, and productivity. Recruitment, training, leadership, engagement, compensation, performance management, workplace well-being, workforce retention, and employee satisfaction are interrelated and can impact service processes, staff retention, and quality of care.